Aggregation and spatio-temporal dynamics of fruit flies (Diptera, Tephritidae) in papaya orchards associated with different area delimitations in Brazil (Acta Scientiarum. Agronomy, 2021)
We investigated aggregation patterns in three fruit fly species economically important in Brazil, namely Ceratitis capitata, Anastrepha fraterculus, and A. obliqua. The study was carried out in a buffer zone and two neighbourhoods by comparing two-time series associated with the management strategy of fruit flies (systems approach). The abundance of these three species significantly decreased over the years with a negative binomial regression model describing the relationship between abundance and time in the entire area, buffer zone, and their neighbourhoods. In addition, the negative binomial model was also well fitted to the frequency distribution data of fruit flies in all analyzed scenarios. Anastrepha obliqua showed the highest aggregation degree, considering both the entire area and time series. A. fraterculus exhibited the lowest aggregation level, and C. capitata showed an intermediate degree. The buffer zone exhibited the highest aggregation degree for all species, and neighbourhood 2 exhibited the lowest aggregation degree. The aggregation degree was higher in the time series impacted by the systems approach than the series in the first years of its implementation.